2016
DOI: 10.1080/15622975.2016.1208841
|View full text |Cite
|
Sign up to set email alerts
|

Separate and combined effects of genetic variants and pre-treatment whole blood gene expression on response to exposure-based cognitive behavioural therapy for anxiety disorders

Abstract: (2016) Separate and combined effects of genetic variants and pre-treatment whole blood gene expression on response to exposure-based cognitive behavioural therapy for anxiety disorders. World Journal of Biological Psychiatry, 18 (3). pp. 215-226. ISSN 1562215-226. ISSN -2975 This version is available from Sussex Research Online: http://sro.sussex.ac.uk/62023/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Full details of data preparation and quality-control procedures are reported elsewhere (Roberts et al, 2017). In order to control for potential population stratification, the first two principal components ("PC1" and "PC2") from genome-wide genotyping data (details reported elsewhere; Coleman et al, 2016) were also tested for association with treatment outcome. Probes were then transformed and normalized, and outliers identified and removed.…”
Section: Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of data preparation and quality-control procedures are reported elsewhere (Roberts et al, 2017). In order to control for potential population stratification, the first two principal components ("PC1" and "PC2") from genome-wide genotyping data (details reported elsewhere; Coleman et al, 2016) were also tested for association with treatment outcome. Probes were then transformed and normalized, and outliers identified and removed.…”
Section: Gene Expressionmentioning
confidence: 99%
“…The receipt, storage and analysis of samples were approved by the London-Bentham NRES Committee and the King's College London Psychiatry, Nursing and Midwifery Research Ethics Sub-Committee.3 | ANALYSES3.1 | Confounding factorsBaseline severity, age, BMI, gender, smoking status, psychoactive medication status, and other medication status were tested for association with percentage reduction in clinical severity and change in DNA methylation between the time-points tested(Tables 1-3). In order to control for potential population stratification, the first two principal components ("PC1" and "PC2") from genome-wide genotyping data (details reported elsewhere;Coleman et al, 2016) were also tested for association with treatment outcome. Variables displaying a significant association with either treatment outcome or change in DNA methylation (p < .05) were included as covariates in the relevant analyses(Tables 1-3).…”
mentioning
confidence: 99%
“…No significant genetic associations with therapy outcome were observed, although three independent loci were of suggestive significance ( P < 5 × 10 −6 ). A second therapy outcome GWAS, which was part of a broader gene expression analysis ( n = 182) also detected several loci that were also of suggestive significance ( P < 5 × 10 −6 ) 41 . Such analyses require large samples to detect small genetic effects at genome-wide significance.…”
Section: Introductionmentioning
confidence: 97%
“…Population stratification was tested for association with outcome using the first two principal components from genome-wide genotyping data (‘PC1’, ‘PC2’). 38 Treated diagnosis was not associated with outcome at post treatment ( F =0.44, P =0.644) or at follow-up ( F =0.74, P =0.480).…”
Section: Methodsmentioning
confidence: 85%
“… 67 To this end, a study from our team showed genotype-dependent changes in FKBP5 DNA methylation associated with treatment outcome. 14 However, in a companion paper to this article combining genome-wide genetic and transcriptomic data (including an extended sample from this cohort 38 ), a number of eQTLs (DNA sequence variation associated with gene expression) were identified, but interactions between genetic variants and treatment response were not significantly associated with expression levels. Nonetheless, future therapygenetics research would benefit from the continued use of genome-wide protocols, and the integration of genetic, epigenetic and transcriptomic information in order to elucidate the potential biological mechanisms underlying psychological treatment response.…”
Section: Discussionmentioning
confidence: 94%